2017
DOI: 10.4103/ejd.ejd_354_16
|View full text |Cite
|
Sign up to set email alerts
|

Hypochlorite solution for root canal irrigation that lacks a chlorinated odor

Abstract: Objectives:This is an in vitro study to develop a formulation of a hypochlorite solution for root canal irrigation that lacks a chlorinated odor. The antibacterial effect, tissue dissolution efficacy, and the cytotoxicity of the solution were assessed in cell culture and were compared with those of commercial sodium hypochlorite (NaOCl) solutions.Materials and Methods:Trichloroisocyanuric acid (TCA) was used as the source of hypochlorite ions in solution. All required properties of the NaOCl irrigant were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 12 publications
(12 reference statements)
0
11
0
6
Order By: Relevance
“…Sodium hypochlorite (NaOCl) is commonly used for root canal disinfection, as a root canal irrigant, which in concentration of 1-6% is able to reduce bacterial infection [27,28,30]. Although NaOCl is commonly used for root canal disinfection, it presents disadvantage such as chlorinated odor, which can be unpleasant for both doctor and patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodium hypochlorite (NaOCl) is commonly used for root canal disinfection, as a root canal irrigant, which in concentration of 1-6% is able to reduce bacterial infection [27,28,30]. Although NaOCl is commonly used for root canal disinfection, it presents disadvantage such as chlorinated odor, which can be unpleasant for both doctor and patient.…”
Section: Discussionmentioning
confidence: 99%
“…A solution of 5.25% sodium hypochlorite (NaOCl-commercial name Chloraxid, Cerkamed, Poland) was used as an antimicrobial agent (irrigant with documented antimicrobial properties) (27) and was considered a positive standard to whom the antimicrobial effects of EO could be reported to. Sterile saline solution was used for negative standard (irrigant without antimicrobial properties).…”
Section: Essential Oils Working Solutions and Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial reduction produced by 2.5% sodium hypochlorite (98.07%) may be explained based on the observations of Rutala and Weber,[ 25 26 27 ] who suggested that, when combined with water, sodium hypochlorite produces hypochlorous acid, which contains active chlorine. Chlorine exerts its bactericidal action through the irreversible oxidation of sulfhydryl groups of essential bacterial enzymes, disrupting the metabolic function of bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Complex root anatomy determines the difficulty of this treatment. The endodontic space has, alongside the root canal, accessory channels, lateral channels, dentinal tubules, apical delta, and is now called an endodontic system [1][2][3][4].…”
Section: Abstract: Irrigation Endovac Organic Detritusmentioning
confidence: 99%